Economic reforms in the industrial sector of the People's Republic of China - Wolfgang Klenner (Intereconomics, 1983)
At the end of the 1970s there occurred a re-orientation of development policy in the People's Republic of China. Changes were introduced in the sectoral development priorities, the guiding principles of the State's incomes and foreign trade policies and in the organization of agricultural production. Above all, initial steps were taken to realign the administrative control system in the industrial sector more towards a market-oriented economic system. This article examines the guiding ideas behind the reform of the industrial sector and the measures taken so far. Emphasis is placed on the introduction of taxation on enterprises' profits which was recently decided and had long been a subject of dispute.
Keywords: 330